THE STRESS RESISTANCE OF STUDENTS. THE PARADIGM OF SUBJECT PERSONALITY SELF- ORGANIZATION - Sergey I. Dyakov (Образование и наука)
The aim of the investigation is to consider a problem of stress resistance of students in the context of subject self-organization of the personality. Methods. The following methods of research are used: questioning; psychological and diagnostic tests «Tolerance of Uncertainty» (NTN) and «Personal Factors of Decisions» (PFD) by T. V. Kornilova; original experimental experiences – «Coding», a technique of a self-assessment (scaling) and «A locus control». While data processing the methods of mathematical statistics (SPSS 12 package) – the correlation analysis of Pearson and the factorial analysis with rotation use a component by «verimax» method are applied. Results and scientific novelty. Types of subjectivity and strategy of stress resistance are allocated. The nature and a role of the emotional and stressful mechanism having information and semantic properties in its basis are disclosed. Communication of irresponsible mechanisms of mentality with the sphere of consciousness in the context of subjectivity of the personality is shown. Mechanisms of emotional and rational self-control of system of mental self-organization of the person are presented. The statistical and qualitative data opening communications between properties of subjectivity and stress resistance of the personality are empirically obtained. Variation of the relations and also types of subjectivity and stress resistance emphasized based on the results of the presented research. Original (author’s) methods of studying of subjectivity and factors of stress resistance are presented. Practical significance. The revealed factors of subject self-organization reveal the stress-producing directions of the environment and the relation of the personality to situations of changes and uncertainty: and also indicate subject properties of resistance to stress which need to be developed to increase the level of health of students, to reduce risk of deviance and delinquency of their behavior.